Peace came in the form of a woman : Indians and Spaniards in the Texas borderlands - Barr, Juliana (University of North Carolina Press, 2007)
Revising the standard narrative of European-Indian relations in America, Juliana Barr reconstructs a world in which Indians were the dominant power and Europeans were the ones forced to accommodate, resist, and persevere.